Diagnostic accuracy of fecal calprotectin for screening patients with colorectal cancer: A meta-analysis - Ye, Xiaohua; Huai, Jiaping; Ding, Jin (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Fecal calprotectin (FC) is reported to have a broad diagnostic accuracy for colorectal cancer (CRC). Therefore, we explored the diagnostic value of FC for CRC using meta-analytical techniques to substantiate the assertion. Materials and Methods: An electronic search of the MEDLINE and Embase databases was conducted to identify studies that assessed the diagnostic accuracy of FC for CRC. The sensitivities and specificities of the eligible studies were summarized using a bivariable random-effects model. Results: In total, 20 studies were included in the final analysis. The pooled sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio of FC for CRC detection were 0.83 (95% confidence interval CI, 0.77-0.88), 0.61 (95% CI, 0.54-0.68), 2.15 (95% CI, 1.82-2.55), and 0.28 (95% CI, 0.21-0.37), respectively. The overall diagnostic odds ratio of FC for CRC was 7.76 (95% CI, 5.41-11.12) with an area under the curve of 0.81 (95% CI, 0.77-0.84), whereas the diagnostic value of FC for colorectal adenoma was relatively inferior (area under the curve, 0.55; 95% CI, 0.51-0.59; diagnostic odds ratio, 1.27; 95% CI, 0.91-1.78). Conclusion: The results imply that the FC test, as currently implemented, cannot be recommended for CRC detection. Cite this article as: Ye X, Huai J, Ding J. Diagnostic accuracy of fecal calprotectin for screening patients with colorectal cancer: A meta-analysis. Turk J Gastroenterol 2018; 29: 397-405.